Effects of low nitrogen supply on nitrogen uptake, assimilation and remobilization in wild bermudagrass - Li, Dandan (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.